2007
DOI: 10.1111/j.1740-0929.2007.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota of ‘airag’, ‘tarag’ and other kinds of fermented dairy products from nomad in Mongolia

Abstract: The traditional fermented dairy products were collected from three nomadic families in Donto‐Govi prefecture in Mongolia (central Mongolia), and those microbiota were analyzed. These samples consist three of ‘airag’, two of ‘tarag’, two of ‘isgelen tarag’ and ‘qoormog’, and some cheeses. In airag, Lactobacillus (L.) helveticus, L. kefiri, and Saccharomyces (S.) dairensis were common, and L. paracasei, L. plantarum, L. farciminis, S. cerevisiae, Issachenkia (I.) orientalis, Kluyveromyces (K.) wickerhamii were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
38
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 13 publications
4
38
3
Order By: Relevance
“…Concerning the minor LAB found in koumiss samples, L. acidophilus, L. delbrueckii, and L. kefi ranofaciens, have been frequently reported in various dairy products Gadaga et al, 2001;Isono et al, 1994;Khedid et al, 2009;Naersong et al, 1996;Uchida et al, 2007). Strains of this group were most relevant to texture properties of the fermented milk for production of acid, folic acid, and exopolysaccharide, and synthesis of vitamins during growth (Forssen et al, 2000).…”
Section: Primermentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the minor LAB found in koumiss samples, L. acidophilus, L. delbrueckii, and L. kefi ranofaciens, have been frequently reported in various dairy products Gadaga et al, 2001;Isono et al, 1994;Khedid et al, 2009;Naersong et al, 1996;Uchida et al, 2007). Strains of this group were most relevant to texture properties of the fermented milk for production of acid, folic acid, and exopolysaccharide, and synthesis of vitamins during growth (Forssen et al, 2000).…”
Section: Primermentioning
confidence: 99%
“…Our experimental results indicated that the average counts of LAB in koumiss were much higher than that of the yeasts. Many researchers have demonstrated the invariable presence of large amounts of yeasts and the dominance role of LAB in koumiss samples (Naersong et al, 1996;Uchida et al, 2007;Watanabe et al, 2008). According to Narvhusa and Godaga (2003), wide distribution of LAB can lead to the specifi c profi les of organoleptic compounds in the milk ecosystem that are important not only for koumiss.…”
Section: Primermentioning
confidence: 99%
“…delbrueckii subsp. bulgaricus.Lactobacillus usually predominated in the traditional naturally-fermented milk Gadaga et al, 2001;Isono et al, 1994;Kamber, 2008;Naersong et al, 1996;Uchida et al, 2007). In this study, Lactobacillus was also considered as dominant LAB strains, which accounted for 35.1% of the total isolates.…”
mentioning
confidence: 99%
“…In the past decade, the microbiota and diversity of LAB species in Mongolian dairy products have been elucidated (Miyamoto et al, 2010;Takeda et al, 2011a;Uchida et al, 2007;Watanabe et al, 2008;Yu et al, 2011). Traditional Mongolian dairy products are consumed not only as important energy sources but also as traditional medicines (Watanabe, 2011).…”
Section: Introductionmentioning
confidence: 99%